2021
DOI: 10.1093/pm/pnab162
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality Meditative Intervention Modulates Pain and the Pain Neuromatrix in Patients with Opioid Use Disorder

Abstract: Objective Standard-of-care for opioid use disorder (OUD) includes medication and counseling. However, there is an unmet need for complementary approaches to treat OUD patients coping with pain; furthermore, few studies have probed neurobiological features of pain or its management during OUD treatment. This preliminary study examines neurobiological and behavioral effects of a virtual reality-based meditative intervention in patients undergoing methadone maintenance treatment (MMT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Regarding pain management, clinical studies have validated the effectiveness of VR as a facilitator of meditation practice in patients with acute pain [ 62 ], chronic pain [ 60 ], and opioid tolerance or opioid use disorder [ 61 , 62 ]. Further neurobiological research studies found that scores for pain, opioid craving, anxiety, and depression decreased after each intervention session (relative to before the session) [ 61 ]. In addition, salivary cortisol (but not CRP) levels were found to decrease from pre- to postsession [ 61 ].…”
Section: Clinical Applicationmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding pain management, clinical studies have validated the effectiveness of VR as a facilitator of meditation practice in patients with acute pain [ 62 ], chronic pain [ 60 ], and opioid tolerance or opioid use disorder [ 61 , 62 ]. Further neurobiological research studies found that scores for pain, opioid craving, anxiety, and depression decreased after each intervention session (relative to before the session) [ 61 ]. In addition, salivary cortisol (but not CRP) levels were found to decrease from pre- to postsession [ 61 ].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Further neurobiological research studies found that scores for pain, opioid craving, anxiety, and depression decreased after each intervention session (relative to before the session) [ 61 ]. In addition, salivary cortisol (but not CRP) levels were found to decrease from pre- to postsession [ 61 ]. Based on pre- to postintervention fMRI assessments, painful task-related left postcentral gyrus (PCG) activation was found to decrease [ 61 ].…”
Section: Clinical Applicationmentioning
confidence: 99%
See 3 more Smart Citations